Emprendimientos que contribuyen en el crecimiento de Clústers empresarial en la ciudad de Riobamba período 2010 al 2014. - Chucho Morocho, Denis Armando (2017)
The present research work emphasizes to “ENTERPRENEURSHIPS THAT CONTRIBUTE IN THE GROWTH OF BUSINESS CLUSTERS IN RIOBAMBA CITY DURING THE PERIOD 2010 - 2014, with the purpose of measuring the enterprising capacity and its contribution to the strengthening of the business clusters of Riobamba city. The investigation is divided into the following four chapters: Chapter I, develops the Frame of Reference, in which consists the exposition and formulation of the problems and objectives of the investigation to be reached. Chapter II, the theoretical Frame is detailed. The same one that is divided into three units: The First Unit includes the general aspects of the company. The Second Unit emphasizes to the entrepreneurship. The Third Unit describes clusters. Chapter III, details the methods that were used for the present investigation, the population and sample, the operationalization of the variables, the techniques and instruments to compile information, the information processing, the analysis and interpretation of results and the Cross-check of the Hypothesis. Chapter IV, develops the conclusions and recommendations, finally it will be possible to demonstrate the results to the raised problems at the beginning of the investigation. There is enclosed also the bibliography and the respective annexes of the investigation.